Acute Toxicity Assessment of Ethyl Acetate Fraction of Melinjo Leaves (Gnetum gnemon L.) on Male Wistar White Rats and Liver Tissue Examination - Herlina, Herlina; Jannah, Miftahul; Permata Wijaya, Dina; Azzahra, Rafifah; Hayati, Ferlina (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: The ethyl acetate fraction of melinjo (Gnetum gnemon L.) leaves has been reported to possess antihyperlipidemic and antidiarrheal activities, and phytochemical screening has identified tannins, phenolics, and flavonoids. However, the safety profile of this fraction remains unclear, necessitating toxicity evaluation. The purpose of this study was to use the fixed-dose method to examine the acute toxicity of the ethyl acetate fraction of melinjo leaves in male Wistar rats. Methods: Based on preliminary testing, the main study used a single oral dose of 2000 mg/kg BW. In silico predictions using Swiss ADMET, Pro-Tox II, and pkCSM showed LD₅₀ values ranging from 159 to 5000 mg/kg. Results: There were no deaths or obvious symptoms of toxicity in either the treatment or control groups, according to observations. Additionally, biochemical analysis showed no significant differences across groups (p > 0.05). The treatment group's mean results were SGPT 76.01 ± 3.20 U/L, SGOT 144.31 ± 34.62 U/L, urea 42.12 ± 7.74 mg/dL, and creatinine 0.622 ± 0.066 mg/dL, while the control group showed SGPT 72.45 ± 11.64 U/L, SGOT 144.19 ± 19.90 U/L, urea 46.08 ± 6.32 mg/dL, and creatinine 0.618 ± 0.024 mg/dL. Macroscopic examination of the liver, kidneys, and heart revealed no pathological changes. Conclusion: At a dose of 2000 mg/kg BW, the ethyl acetate fraction of melinjo leaves did not cause acute toxicity, indicating a good safety profile for further pharmacological research.